The sweet singer of Israel: Isaac Watts and the developing hermeneutic of nonconformist psalmody - Johnson, Daniel (2016)
This thesis assesses the contribution made by Isaac Watts to the developing hermeneutic of Nonconformist psalmody. Prior to Watts, Nonconformist psalmody was dominated by the enduring influence of John Calvin. Chapter One traces the history of Nonconformist psalmody from Calvin to Watts, as well as briefly summarising the hermeneutic of the Psalms when preached in the later seventeenth century. Chapter Two discusses Watts’ Short Essay Toward the Improvement of Psalmody, where he outlines his methodology for converting the Psalms into hymns for the Christian church. Chapter Three looks at the way Watts uses Scripture in his Psalter, before considering his Christology. Chapter Four examines Watts’ view of the reign of Christ within the Psalms, and its relationship to the Church, Israel and Britain.